Pharmacokinetics and bone tissue concentrations of lincomycin following intravenous and intramuscular administrations to cats - Albarellos, Gabriela Alejandra (2011)
The pharmacokinetic properties and bone concentrations of lincomycin in cats after single intravenous and intramuscular administration at a dose rate of 10 mg/kg were investigated. Lincomycin minimum inhibitory concentration (MIC) for some gram-positive strains isolated from clinical cases was determined. Serum lincomycin disposition was best fitted to a bicompartmental and a monocompartmental open models with first-order elimination after intravenous and intramuscular dosing, respectively.  After intravenous administration, distribution was rapid (T½ (d) 0.22±0.09 h) and wide as reflected by the volume of distribution (V(d(ss))) of 1.24±0.08 L/kg. Plasma clearance was of 0.28±0.09 L/h.kg and elimination half-life (T½) of 3.56±0.62 h. Peak serum concentration (Cmax), Tmax and bioavailability for the intramuscular administration were 7.97±2.31 µg/mL, 0.12±0.05 h and 82.55±23.64% respectively. Thirty to 45 minutes after intravenous administration, lincomycin bone concentrations were 9.31±1.75 µg/mL. At the same time after intramuscular administration, bone concentrations were 3.53±0.28 µg/mL. The corresponding bone/serum ratios were 0.77±0.04 (intravenous) and 0.69±0.18 (intramuscular). Lincomycin MIC for Staphylococcus spp ranged from 0.25 to 16 µg/mL and for Streptococcus spp from 0.25 to 8 µg/mL.